Fighting Auschwitz : the resistance movement in the concentration camp - Garliński, Józef 1913-2005 (Aquila Polonica (U.S.) Ltd, 2018)
Abbreviations --Introduction /Professor Antony Polonsky --Foreword /Professor M. R. D. Foot --Preface --Part One --Chaper 1 --Voluntarily to Auschwitz --Undercover Mission --The German Plans for Auschwitz --Construction and Early Days of Auschwitz --Witold Pilecki Arrives in Auschwitz --Organization and Admininstration of the Auschwitz Camp --Use of Prisoners in the Camp Administration --Himmler's Visit to Auschwitz --Notes to Chapter 1 --Chapter 2 --The Development of Underground Work in the Camp --The First 'Five' --The Polish Underground --Notes to Chapter 2 --Chapter 3 --The Underground Organization in the Neighbourhood of the Camp --Secret Wkork in the Hospital --The First Reports to London --The Organization of Labour and Underground Workers in Key Positions --The Orchestra; Collective Responsibility for Escapes --The German-Soviet Union War --Notes to Chapter 3 --Part Two --Chapter 4 --The First Deaths from Gassing --The Fourth 'Five' --Agreement Between the Military and Political Groups --The Building of Birkenau --Slave Labour in Auschwitz and Sub-Camps --The Extermination of the Jews --Notes to Chapter 4 --Chapter 5 --The Underground Network in Birkenau --Pilecki's Contact with the Czechs --The Radio Transmitter --The Underground's First Escapes --Revolt in the Penal Companies --Further Unification of the MIlitary Groups --Notes to Chapter 5 --Chapter 6 --The Women's Camp --The Hospital --Liquidation of Informer's --Reassignment of Military Leadership --Himmler's Second Visit --Notes to Chapter 6 --Chapter 7 --Losses Among the Underground --Help from Outside the Camp --The Partisan Units --Pilecki's Escape --Pilecki Reports to His Home Army Superiors --Notes to Chapter 7 --Part Three --Chapter 8 --Summary of the Previous Period --Underground Leadership After Pilecki's Escape --Overview of Nationalities and Ethnic Groups at Auschwitz --The Austrian Group --The French Group --The Soviet Group --Other Groups --Formation of the Kampfgruppe Auschwitz --Notes to Chapter 8 --Chapter 9 --The Surveyors' Kommando --SS Morale --Conditions in the Hospital --Liquidation of the Leaders of the Polish Military Underground --The New Commandant and Changes in the Camp --Influence of Hermann Langbein --Notes to Chapter 9 --Chapter 10 --Further Action by the Underground --Changes at the Hospital; Obliterating Traces of Crimes --The Book the Bunker --Liquidation of Hungarian Jews --Changes in the Underground --Notes to Chapter 10 --Chapter 11 --Escapes and Partisans --The Moll Plan --The Revolt in the Sonderkommando --Preparations for the Relief of the Camp --The Underground's Final Actions --Evacuation --Notes to Chapter 11 --Conclusion --Afterword /Jarek Garlinski